The Geology of Fannich Forest - Winchester, J; Winchester, J. A. (1970)
﻿ Fannich Forest consists geologically of a complex of Moinian and Lewisian rocks. The area was mapped, and from the field-evidence a stratigraphy and structural interpretation were worked out. The structural interpretation was fitted into a regional interpretation of Moinian structure in Western and Central Ross. The petrology of the different rock-types was studied and used to assess the metamorphic grade of the area, while geochemical evidence strongly suggested that a Lewisian Inlier is present in Fannich. Mapping showed that the Lewisian inlier extends south of Loch Fannich on Beinn nan Ramh and on Moine Mor. The stratigraphic succession worked out is tabulated below: Sgurr Mor Pelite Psammites Meall an t-Sithe Pelite Moinian UNCONFORMITY Silicic Gneisses and Amphibolite Lewisian Complex early folding caused these units to form a repetitive succession deformed by the readily visible structures in the area. Three fold-events have occurred: F1 folding initiated the formation of an isoclinal anticline with a Lewisian core, and a complementary isoclinal syncline, exposed at present with Sgurr Mor Pelite in its core. F2 folds refold the Lewisian of Fannich in near-isoclinal folds, and a larger F2 fold may refold the main F1 anticline so that it now closes east. F3 folds, with axial traces broadly trending north-south, are asymmetrical open folds, deforming the foliation developed in the rock during the previous fold-events. They deform an apparent succession in which the Lewisian core of the F1 anticline forms the second-highest unit. The most important of these folds is the Fannich Synform. Since the Sgurr Mor Pelite occurs in the core of an F1 syncline, open to the east, the Lewisian of Fannich is separated from the Lewisian of the Central Ross-shire Inliers. It is considered to form part of the upper limb of the refolded Moine (=Morar) Nappe, and to underlie the postulated Central Ross-shire Nappe. It is admitted that sliding may have occurred in Fannich, but the available evidence in Fannich does not require such a slide in order to explain the regional structure. Petrological studies reveal differences in mineralogy and texture between Lewisian and Moinian amphibolites; differences also occur between different amphibolite groups within the Moinian, which are considered to originate from different magmas. In calo-silicate strips from the Sgurr Mor Pelite, a reaction in which biotite forms from hornblende was observed, often accompanied by a reaction forming zoisite at the expense of plagioclase. It was found to be directly influenced by the CaO/Al2O3 ratio of the rock. The different ratios at which this reaction proceeded in different places are considered to indicate differences of metamorphic grade. The reaction is retrogressive; the apparent increase of grade with increasing altitude is more probably a result of lessening influence of second, retrogressive metamorphism with increasing height, thus allowing the original (higher-grade) mineralogy to be preserved more fully. Breakdown of kyanite in politic schist, and the accretion of calcic rims around almandines, were also interpreted as signs of retrogression. Electron probe microanalysis of almandines from pelite suggested that much of western Fannich may have been subjected to sillimanite-grade metamorphic conditions, and that the subsequent milder metamorphic episode induced retrogression. By analogy with Morar, places where the hornblende-biotite reaction in calc-silicates occurs at a CaO/Al2O3, ratio of 0.4, are approximately on the kyanite isograd. The metamorphic grade now preserved in Fannich is of almandine grade in the north and east, and mainly kyanite grade in the south-west and centre. The earlier metamorphic episode reached maximum intensity about the time of F2 folding, while the milder late event probably accompanied F3 deformation. In this respect, as in others, the structural and metamorphic history of Fannich is comparable to that of other Moinian areas. Geochemical evidence reveals differences between Moinian and Lewisian rocks that are not eliminated by metamorphism. Silicic gneisses and amphibolites from the Lewisian rocks contain FeO/TiO2, K/Rb ratios and zirconium contents different from those of the Moinian, but often resembling those of rocks from the Lewisian Foreland, west of the Moine Thrust. Alteration of these ratios and Increase in zirconium content during sedimentation accounts adequately for the overall persistent differences in composition between Moinian and Lewisian rocks. The very high FeO/TiO2 ratio of the Lewisian rocks suggests that they may be Scourian, rather than Laxfordian gneisses. Increase in K2O content and decrease in the FeO/TiO2 ratio observed in the Lewisian near the junction with the Moinian is tentatively attributed to the effects of weathering of the Lewisian before the deposition of the Moinian. Some K2O enrichment of the Lewisian may also have occurred during metamorphism, resulting in the secondary growth of biotite in the amphibolites, but little other evidence of metasomatism was seen. Therefore the present chemical composition of the Moinian rock-units is considered to be broadly that of the original sediments. Chemical evidence was used to confirm petrological evidence that Lewisian rocks occur in Fannich, both where previously mapped, and south of Loch Fannich, and the interpretations of the structure are based on this conclusion.